Evaluation of the Impact of the Provision of Triple Combination Antiretroviral Therapy to Employees Through the In-House Health Programme at a Large South African Mining Company - Brink, Jonathan Edward (School of Economics, 2019)
HIV/AIDS poses a unique challenge to businesses, particularly those operating in Southern Africa. The region is home to one third of the worldwide HIV positive population (as measured by those aged 15 to 49) yet as a whole contributes a diminutive proportion of the total worldwide population by the same measure (UNAIDS, 2016; World Bank, 2016). Relative to its size, the epidemic has introduced disparately large economic strain due to the fact that the highest HIV prevalence rates coincide with the most productive years of people’s lives, with prevalence rates peaking around the 30 to 34-year-old stratum (Shisana, et al., 2012). Loss of business productivity as a result of HIV related illness through a combination of absenteeism and so called ‘presenteeism’1 as well as death due to AIDS and the resultant increase in employee turnover, has motivated companies to implement workplace HIV education, prevention and treatment programmes over and above governments’ efforts to curb the effect of the disease on business operations and the associated economic costs (Granich et al., 2012; Meyer-Rath et al., 2012, 2015).